2012
DOI: 10.2174/187221112802652633
|View full text |Cite
|
Sign up to set email alerts
|

Single Emulsion-Solvent Evaporation Technique and Modifications for the Preparation of Pharmaceutical Polymeric Nanoparticles

Abstract: In recent years, there has been an increased interest in using nanoparticles for drug delivery and pharmaceutical development. Nanoparticles can offer significant advantages over the conventional drug delivery systems in terms of high drug loading, stability and specificity, controlled release capability, and the ability to deliver both hydrophilic and hydrophobic drug molecules through various routes of administration. This review article focuses on the use of the single emulsion solvent evaporation method, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 0 publications
0
34
0
1
Order By: Relevance
“…This behavior indicates the fully water‐soluble solvents (acetone and ethanol) have faster diffusion speeds and avoid aggregation of nanodroplets in the emulsion. On the contrary, the immiscible nature of ethyl acetate in water leads to large particle sizes . Comparing acetone and ethanol as organic additive, the size was smallest using acetone due to polarity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This behavior indicates the fully water‐soluble solvents (acetone and ethanol) have faster diffusion speeds and avoid aggregation of nanodroplets in the emulsion. On the contrary, the immiscible nature of ethyl acetate in water leads to large particle sizes . Comparing acetone and ethanol as organic additive, the size was smallest using acetone due to polarity.…”
Section: Resultsmentioning
confidence: 99%
“…Particle size is an important property which can improve and/or facilitate the interaction with biological substrates. The emulsion‐solvent evaporation method is one of the most used in hydrophobic drug encapsulation and nanoparticle preparation with amphiphilic polymers . Studies have showed that some factors such as polymer concentration, pH, stirring time, homogenization method and organic solvent affect the size, polydispersity, and efficiency of drug encapsulation of the self‐assembled nanoparticles …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…89, 90 When properly optimized, these polymeric carriers may serve as a highly functional delivery vehicle for mRNA. The surfaces can be easily modified with other materials such as ligands to confer targeting abilities and other polymers to afford properties such as pH-responsive release for tuning the release profile.…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
“…Surfactants are usually incorporated in the aqueous phase and they are hydrophilic polymers, anionic or cationic surfactants. The most commonly reported surface active polymers for producing EC nanoparticles are: (1) low molecular weight surfactants: sodium dodecyl sulfate (Desgouilles et al 2003;Urbán-Morlán et al 2015) sorbitan monolaurate-Span 20 (Spernarth and Magdassi 2007), decaglycerol monolaurate (Spernarth and Magdassi 2007), lauryl ether (Wachsmann and Lamprecht 2015), cetyltrimethylammonium bromide (Wachsmann and Lamprecht 2015) and (2) polymer based surfactants: polyvinyl alcohol (PVA) (Nava-Arzaluz et al 2012), polyethylene glycol sorbitan monolaurate-Tween 20 (Gunduz et al 2012), (Wondraczek et al 2013), polyoxyethylene (23) (Wachsmann and Lamprecht 2015), polysorbate 20 (Wachsmann and Lamprecht 2015), poloxamer 188 (El-Habashy et al 2016), cremophor A25 (El-Habashy et al 2016). Although already various different surfactants were tested in the EC nanoparticle preparation, to the best of our knowledge, the potential of ionic, nonionic and amphiphilic polysaccharide surfactants to design differently shaped EC nanoparticles were not investigated yet.…”
Section: Introductionmentioning
confidence: 99%